O currículo praticado no contexto do programa mais educação: concepções, práticas e limitações da educação integral - Souza, Vinícios Rocha de (2017)
This thesis aimed to understand the process of creating and defining the integral education school curriculum and, consequently, the redefinition of the operandi modes of pedagogical action of a public basic education school in the city of Fortaleza, which joined the Programa Mais Educação - PME, in line with the study of the curricular experience during this school period. The PME was established in 2007, with the aim of promoting the integral education of children and young people, through socio-educational activities, linked to the schools' teaching project. To this end, we carried out qualitative case study research, with an ethnomethodological approach. We carried out the study in a municipal school in Fortaleza. The research participants were the school's social actors (managers, Mais Educação monitors and students). The theoretical framework and understanding of the integrated curriculum was based on the possibility of reading the rhizomatic perspective proposed by Deleuze & Guatarri (1995) and the concept of autopoiesis elaborated by Maturana & Varela (2004). The stages of the research were Reading and critical interpretation of Political-Pedagogical Projects in an attempt to understand the didactic-pedagogical intentions of the school curriculum in relation to work with integral education; then, monitoring of curricular activities using observational techniques to understand the procedures and experiences of the integral education curriculum; and, finally, semi-structured interviews with managers and teachers, and a focus group with students to characterize knowledge and practices, in order to understand curricular integration. The results obtained demonstrated that the PME carries out its intention of comprehensive education within the school from an almost exclusive perspective of after-school education. The socio-educational activities aimed at students do not have direct articulation with the political pedagogical project - PPP or with other school activities. They therefore pointed to the fact that there was no global reorganization of knowledge and actions in the school, in the context of the PME, around the objective construction of a comprehensive and integrated education curriculum, in these years of the institution's participation in the program. However, from the point of view of our reflection on the actions, attitudes, knowledge and speeches of the monitors and students, it was possible to identify paths taken and constructed in which some transversal integrations were established.